PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN KONSUMEN MINUMAN KOPI (SUATU KASUS DI KEDAI KOPI HARUM MANIS KARANG TENGAH KOTA TANGERANG) - Bintang Kejora; Suherman Suherman; Ratna Mega Sari (JURNAL AGRIBISNIS TERPADU, 2022)
The coffee shop business category has a large market opportunity so that many competing companies enter and compete in this business competition so that the competition is getting tougher. The Harum Manis coffee shop, Karang Tengah, Tangerang City needs to have a marketing strategy that can be applied in marketing its products. This study aims to analyze the influence of the marketing mix simultaneously and partially on consumer satisfaction and identify the influence of the most dominant variables. Research The method used in this research is a survey method. The sampling technique is to obtain respondents as many as 100 people. Multiple linear regression data analysis. The coefficient of determination (R2) shows that the independent variables studied are able to explain 32.9% of the consumer variables, the remaining 67.1% satisfaction is explained by other variables not examined in this research factor. The results of the partial test (t test) explain that the independent variables consisting of product, price and promotion individually or partially have a significant influence on the dependent variable, namely customer satisfaction with coffee drinks and results. Simultaneous testing (Test F) explains that the independent variables consisting of product, price, place, promotion, people, process, and physical evidence variables together or simultaneously have a significant effect on the customer satisfaction variable for coffee drinks. The most dominant variable is promotion (20.67%).